STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAKUL KARIMAH SISWA DI SMP ISLAM DARUSSA’ADAH TUMPANG MALANG - Muhammad Zainuddin; Chalimatus Sa’dijah; Ika Anggraheni (VICRATINA, 2019)
Islamic Education Teachers play an important role in carrying out their duties, namely in the process of fostering morality to students.  expected to obtain maximum moral development results.  The teacher is expected to be able to apply various kinds of strategies in shaping the morality of the heart.  Students who have good morality always show good behavior in relationships with God, relationships to people, relationships to the environment and relationships with themselves.  and the determination of the strategies of Islamic Education teachers in conducting student moral development.  Based on that, researchers conducted research at Darussa'adah Islamic Middle School with the title of the strategy of Islamic religious education teachers in the formation of students' moral virtues.